High-intensity interval training programme for obese youth (HIP4YOUTH): A pilot feasibility study. Issue 18 (17th September 2017) - Lee, SoJung; Spector, Jenna; Reilly, Stephanie
ABSTRACT: Recently, there has been growing interest in high-intensity interval training (HIT) as a strategy to improve health. In this pilot study, we examined the feasibility of a 4-week low-volume HIT and its effects on cardiorespiratory fitness (CRF), blood pressure (BP) and enjoyment in overweight and obese youth. Twelve adolescents (body mass index (BMI): 34.8 ± 3.9 kg · m ‒ 2, 14.9 ± 1.5 years) participated in 12 sessions of HIT (10 × 60 s cycling bouts eliciting ~90% maximal heart rate, interspersed with 90 s recovery, 30 min/session, 3 sessions/week) over ~4 weeks. All the participants completed the study and exercise attendance averaged 92%. Despite no changes in body weight and total fat, HIT resulted in significant ( P  < 0.01) increases in CRF (pre: 20.1 versus post: 22.2 ml · kg ‒1 · min ‒1 ) and exercise time (pre: 425 versus post: 509 s) during peak oxygen uptake test, and a reduction in resting systolic BP (pre: 115.8 versus post: 107.6 mmHg). The majority of study participants (83%) enjoyed HIT and more than half of the participants (58%) reported that HIT is a more enjoyable form of exercise compared to other types of exercises. Low-volume HIT is a useful strategy to promote exercise participation and improve cardiovascular health in overweight and obese youth.